DATABASE ENGINEERING AND BUSINESS - Tello Y., Roberto (2003)
The article shows an analysis of all applications that can be used by the data base models referring to engineering and business process. It is emphasize the importance of modeling of the database and two phases of training of Data Base is proposed.